PENDEKATAN HOLISTIK PADA TUMBUH KEMBANG ANAK - RAFSEL TAS'ADI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Basically, human growth is in line with their development. This implies that if the growth taking place within individuals runs well, so does the development. Growth and development experienced by the individuals are unique since they are influenced by several factors which are different from one individual to the others. In general, those factors are religious (spiritual), organobiologic, social and cultural, psycho-educative. In terms of educational practices, none of those factors, in holistic approach, is ignored. Therefore, parents or educators should have comprehensive understanding those factors in order to promote optimum growth and development of children.Kata kunci: Pendekatan holistik dan tumbuh kembang anak